Uncertainty in acoustics : measurement, prediction and assessment - Peters, Bob, 1944-2019 (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
"This guide to estimating uncertainties in the measurement, prediction and assessment of noise and vibration applies across environmental noise and vibration, occupational noise and vibration exposure, and building and architectural acoustics. The book collates information from the various standards and from research, with explanation, examples and case studies. It enables estimation of uncertainty in the measurement and prediction of acoustic quantities, suitable for use in environmental impact and occupational exposure assessments. It is for acoustic consultants, mechanical and building service engineers, architect and building professionals and environmental health officers. Emphasizes practical advice on the estimation of uncertainties. Includes examples and case studies consistent with the provisions of the relevant standards. Suits a wide range of specialisms across acoustics Unique extensive presentation of scattered materials"--
Introduction to uncertainty in acoustic measurements / Robert Peters -- Measurement uncertainty associated with sound and vibration instrumentation / Ian Campbell -- Uncertainty in the prediction of sound levels / Roger Tompsett.
OCLC-licensed vendor bibliographic record.
Keywords: Acoustic models; Sound -- Measurement; Measurement uncertainty (Statistics); TECHNOLOGY / Acoustics & Sound; TECHNOLOGY / Engineering / Mechanical